Analisis Consumer Rating dan E-Trust terhadap Continuance Intention (Survei pada Pengguna Aplikasi Netflix di Kota Sukabumi) - Shafrizal Muhammad Zen; Asep Muhamad Ramdan; Tetty Sufianty Zafar (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
The rapid growth of subscription-based digital streaming services has intensified competition among video-on-demand platforms, making user retention a critical challenge. In this context, consumer rating and electronic trust are considered important factors influencing users’ continuance intention. This study aims to analyze the effect of consumer rating and e-trust on continuance intention among Netflix application users in Sukabumi City, Indonesia. A quantitative approach was employed using an associative research design. Data were collected through an online questionnaire distributed to 300 Netflix users selected using purposive sampling. The data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS) through SmartPLS 3.2.9. The results indicate that consumer rating has a positive and significant effect on continuance intention, suggesting that favorable evaluations from other users strengthen users’ willingness to continue using the platform. Furthermore, e-trust also shows a positive and significant influence on continuance intention, reflecting that trust in service reliability, data security, and system integrity enhances long-term usage intention. Overall, the findings highlight the importance of maintaining credible rating systems and strengthening digital trust to sustain user engagement in subscription-based streaming services.